SIMULATION BASED APPRAISAL STUDY OF OSPF AND EIGRP FOR EFFECTIVE COMMUNICATION NETWORK (FUDMA JOURNAL OF SCIENCES, 2023)
Today, internet is playing a vital role in communication networks and this computer communication networks are based on technology that provides technical infrastructure, where routing protocols are used to transmit packets across the network. The Open Systems Interconnection (OSI) reference model was created, to determine the compatibility of various connected devices for communication. The routing protocols are implemented in the network layer of the model, providing the set of rules for devices to route data packets towards the destination. This paper focuses on two (2) routing protocols: Open Shortest Path First (OSPF) and Enhanced Interior Gateway Routing Protocol (EIGRP) which is a member of Interior Gateway Protocol (IGP). Different protocols use different algorithms to route its packets and this affects the overall performance of the network. OSPF and EIGRP were used to distribute routing information between routers in the same autonomous system. Extensive experiments have been conducted to analyze and compare a set of characteristics of OSPF and EIGRP on an application like video Conferencing by using OPNET Modeler in an enterprise partial mesh network topology to determine the best protocol for a fast network convergence. Hence, this research simulates three network topologies and the results clearly show that EIGRP converges faster than OSPF and also EIGRP has the least Point to Point Queuing Delay than OSPF.
Keywords: OSPF, EIGRP, OPNET Modeler, Simulation, Routing Protocols